Anger Management in Adolescents: A Systematic Review - Shamala Anjanappa; Radhakrishnan Govindan; Manjula Munivenkatappa (Indian Journal of Psychiatric Nursing)
Children and adolescents lack adequate skills to recognize and cope with the feelings of anger, which is often displayed in the school setting in the form of disruptive behaviors. Training adolescents with anger management skills reduces the negative outcomes related to anger issues. The objective of review is to provide comprehensive overview of anger management interventions for adolescents. Search was done using electronic databases such as Cochrane Library, OVID Medline, PubMed, CINAHL, EBSCOhost Springer, Wiley Online Library, ProQuest, ScienceDirect, and PsycINFO. Total 212 studies were found on anger management; twelve studies (five meta-analysis, one randomized controlled trial, one mixed methods, and five experimental) fulfilled the inclusion criteria of the study and these studies were included in the systematic review. Majority of the studies used cognitive behavioural therapy (CBT) as predominant therapeutic strategy for anger management for adolescents. Only few studies included rational emotive behavior therapy, social skill training, and education on anger. CBT with problem-solving skill training, communication skill training, and self-instruction was found to be effective in reducing anger problems in adolescents.